Development of Value-Added Products in Aquaculture - T. Morrissey, Michael (Avances en Nutrición Acuicola, 2011)
Aquaculture is becoming increasingly important in satisfying consumer demands for good quality seafood. It has maintained a steady, positive growth over the years when compared to marine fisheries and is supplying the nutritional needs for both developed and developing countries. While aquaculture has supplied fresh fish and shellfish to global markets, there is an increasing opportunity for expanding value-added products. There are several advantages to value-added processing, including creating safer products, preserving high quality characteristics, extending shelf-life and enhancing economic return to the producer/processor. Value-added products can come in several forms including traditional processed products; market-driven products that have a steady or increasing demand; health-driven seafood, which is becoming an increasingly important niche, values-driven product that is focused more on environmental concerns and social issues, and technology-driven seafood products which often adds safety as well as quality characteristics to products. These different opportunities for aquaculture will be discussed in detail. Value-added processing will play an important role in the growing aquaculture sector to help meet demands of the consumer for safe, wholesome, high-quality seafood products.